Illegal and unmanaged aquaculture, unregulated fisheries and extreme climatic events combine to trigger invasions in a global biodiversity hotspot - Raj, Smrithy; Kumar, A. Biju; Tharian, Josin; Raghavan, Rajeev (Biological invasions, 2021)
Focusing on extreme climatic events in India’s Western Ghats Biodiversity Hotspot, we demonstrate that unmanaged aquaculture and unregulated fisheries can often combine with ECE in exacerbating biological invasions through the unexpected introduction and escape of novel alien species. High magnitude flooding events in August 2018 and 2019 resulted in the escape of at least ten alien fish species that were recorded for the first time, from the natural waters of the Western Ghats. Illegal farming systems, aqua-tourism destinations and amusement parks, as well as reservoirs, facilitated the escape of alien species during the ECE. Despite expanding invasions, unmanaged stocking and aquaculture using alien species continue in the Western Ghats, necessitating urgent management and policy interventions.